2000
DOI: 10.1111/j.1349-7006.2000.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of S‐Methylcysteine and Cysteine on the Promoting Potential of Sodium Phenobarbital on Rat Liver Carcinogenesis

Abstract: The effects of S-methylcysteine (SMC) and cysteine on the promotion stages of rodent hepatocarcinogenesis in a medium-term bioassay previously developed by Ito were examined. Initiation was induced by a single dose of diethylnitrosamine (DEN), followed by dietary administration of the promoter sodium phenobarbital (NaPB) 2 weeks later, for 6 weeks. Partial hepatectomy was conducted on all the animals at week 3. Inhibitory potential was evaluated by analyzing two markers of carcinogenesis, namely numbers of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…On average, absolute liver weights and relative liver weights (liver weight/body weight) in groups B, C, and D, all receiving diets containing PB, were greater than in other groups (18.9 vs 16.7 g and 0.0347 vs 0.0301 g/g). We noted that the carcinogenesis promoter PB, a potent mitogen in hepatocytes, increased cell cycling within GST-P-positive foci resulting in hypertrophy and/or hyperplasia [21,23].…”
Section: Effects In Vivomentioning
confidence: 98%
See 1 more Smart Citation
“…On average, absolute liver weights and relative liver weights (liver weight/body weight) in groups B, C, and D, all receiving diets containing PB, were greater than in other groups (18.9 vs 16.7 g and 0.0347 vs 0.0301 g/g). We noted that the carcinogenesis promoter PB, a potent mitogen in hepatocytes, increased cell cycling within GST-P-positive foci resulting in hypertrophy and/or hyperplasia [21,23].…”
Section: Effects In Vivomentioning
confidence: 98%
“…Accordingly, we initiated hepatocarcinogenesis with DEN enhanced by coadministration with phenobarbital (PB) [21,22] in rats subsequently treated with PC and MK-4. Immunohistochemical morphometric analysis was directed at glutathione S-transferase (GST-P), a marker for preneoplastic change in hepatocytes [23] that has become established in quantitative analysis of the process of hepatocarcinogenesis in rats [21,[24][25][26]. Some papers reported PC had protection potential toward liver injury by CCL4 [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several previous reports have documented a wide range of activities of garlic and its components, particularly SMC, for treatment of various physiological and pathological conditions [ 24 , 25 , 26 ]. In this regard, some previous reports revealed that garlic, SMC, and other organosulfur compounds of raw or extracted garlic showed anticancer [ 27 ], antioxidant [ 28 ], anti-inflammatory [ 29 ], antidiabetic [ 30 ], cardioprotective [ 24 ], neuroprotective [ 31 ], hypocholesterolemic [ 30 ], antiinfective [ 32 , 33 ], and hepatoprotective effects [ 34 , 35 , 36 ]. To the authors’ knowledge, no former investigations assessed the effect of SMC against C. parvum either in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…animals 6,17,23 . Using rats from Japan Charles River Co., it is well known that numbers and areas per cm 2 of GST-P positive foci in the liver in the Ito test are increased significantly in PB treated rats compared with control groups given DEN alone 7,[14][15][16][17][18][24][25][26][27] . According to those studies, the number of GST-P positive foci in the liver of control groups ranged from 3.6 ± 1.8 to 5.8 ± 2.4; the area of GST-P positive foci in the livers of control groups ranged from 0.24 ± 0.23 to 0.56 ± 0.35; the number of GST-P positive foci in the livers of PB-treated groups ranged from 7.2 ± 2.8 to 13.9 ± 2.9; and the area of GST-P positive foci in the livers of PBtreated groups ranged from 0.94 ± 0.61 to 1.76 ± 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…We compared these rats for hepatocarcinogenic effects of PB, using a medium-term rat liver bioassay system, the Ito test 5,6,12,13 . PB has been used as a positive carcinogen control [14][15][16][17] , and to examine the dispersion of effects among animals from different breeders is useful.…”
Section: Introductionmentioning
confidence: 99%